Mathematical model of combined parametrical analysis of in indicator process and thermal loading on the diesel engine piston - Lebedevas, Sergejus; Lebedeva, Galina (Transport, 2004)
In the publication the methodical aspects of a mathematical model of the combined parametrical analysis of an indicator process and thermal loading on the diesel engine piston have been considered. A thermodynamic model of a diesel engine cycle is developed. The executed development is intended for use during researches and on the initial stages of design work. Its realization for high revolution diesel engines of perspective type CHN15/15 allowed to choose rational variants for the organization of an indicator process and to prove power ranges of application for not cooled and created cooled oil welded pistons.First Published Online: 27 Oct 2010